Model Pembelajaran Problem Based Learning dalam Meningkatkan Inovasi Siswa pada Mata Pelajaran Pendidikan Agama Islam SMP di Kota Bogor - Gunarti Sukriyatun; Endin Mujahidin; Hendri Tanjung (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research aims: 1) to determine current innovation students for junior high school in Bogor City. 2) Develop Problem Based Learning model to improve students for junior hight school Bogor City.  3) Determine the effectiveness of PBL model in improving students for junior hight school Bogor city innovation. This research is based on the development research by Borg and Gall with three research and development stages, preliminary study, model development, and model test. The data analysis used during the development research were descriptive analysis, model validation analysis, and model effectiveness analysis with t-test independent samples. The results of the research concluded that: the innovation of students for junior high school Bogor City is currently low and needs to be improved; the developed model is declared "fit foruse" by learning experts with more notes. The PBL model is declared effective in increasing the innovation  students for junior highschool in Bogor City.